Strengthening the Retribution System for Waste Management Services in Indramayu Regency Policy Review and Implementation Challenges - Rizkiyah, Wiji Febriyani; Soleh, Soleh (Universitas Wiralodra, 2025)
Waste management at the regional level remains a multidimensional challenge encompassing fiscal, institutional, and social dimensions. This study analyzes the waste service fee system in Indramayu Regency to identify its main barriers and propose practical reform measures. Using a descriptive-qualitative approach supported by regulatory and institutional analysis, the research draws on secondary data from laws, budget documents, the 2024 tariff update report, and a Focus Group Discussion (FGD) with relevant stakeholders. The findings indicate that the current system achieves only 14–20% cost recovery, with tariffs far below actual service costs. Institutional weaknesses are evident in fragmented roles between the Environmental Agency (DLH), the Waste Management UPTD, and the Regional Revenue Agency (Bapenda), resulting in poor data integration and ineffective collection. Public compliance also remains low due to negative perceptions of service quality, perceived unfairness in tariff structures, and limited transparency in fund management. Strengthening the system requires phased reforms, including tariff recalibration, database integration, service quality improvements, and stronger public communication. With these measures, Indramayu’s fee system can evolve into a sustainable and accountable foundation for regional waste governance.